PENINGKATAN PEMAHAMAN SISWA MELALUI MEDIA POWER POINT DENGAN PEMBELAJARAN RME PADA PEMBELAJARAN MATEMATIKA KELAS 6 MENUJU MASYARAKAT 5.0 DI SDN 13 MUARA TELANG - Robiyono, Robiyono (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract — Facts based on the results of the initial dialogue with grade 6 teachers and observations, at SDN 13 Muara Telang show that the quality of the learning process in the classroom is still not optimal both in terms of students, teachers, media and learning methods. Teachers still tend to use the lecture method in delivering subject matter without adequate support. Students also tend to be passive in learning activities and there is no active role of students in educational interactions in class, students only act as objects in learning and sometimes even reluctant and indifferent in following the learning process. As a result of the lack of optimal learning process is the understanding of student concepts that tend to be low. Therefore the teacher uses PowerPoint as a medium that is combined with realistic mathematics education (RME) learning. If you pay attention to the level of student understanding and student interest in mathematics tends to be low. Out of 30 6th grade students, only 25% can attend math material, 25% lack enthusiasm, and 50% look indifferent and tend to make noise. By looking at the results of the assessment it was true that student learning outcomes are still below the Minimum Mastery Keriteria standards.Keywords— powerpoint, realistic mathematics education, Student Understanding  Abstrak— Fakta berdasarkan hasil dialog awal dengan guru kelas 6 dan observasi, di SDN 13 Muara Telang menunjukkan bahwa kualitas proses pembelajaran di kelas masih kurang optimal baik dari segi siswa, guru, media maupun metode pembelajaran. Guru masih cenderung menggunakan metode ceramah dalam menyampaikan materi pelajaran tanpa adanya dukungan yang memadai. Siswa juga cenderung pesif dalam kegiatan pembelajaran dan belum ada peran aktif siswa dalam interaksi edukatif dikelas, siswa hanya bertindak sebagai obyek dalam pembelajaran bahkan terkadang enggan dan acuh dalam mengikuti proses pembelajaran. Akibat kurang optimalnya proses pembelajaran ini adalah pemahaman konsep siswa yang cenderung rendah. Oleh karena itu guru menggunakan media PowerPoint sebagai media yang dipadukan dengan pembelajaran realistic mathematics education (RME). Jika diperhatikan tingkat pemahaman siswa dan ketertarikan siswa terhadap matematika cenderung rendah. Dari 30 siswa kelas 6 hanya 25% yang dapat mengikuti materi matematika, 25% kurang bersemangat, dan 50% terlihat acuh dan cenderung membuat kegaduhan. Dengan melihat hasil penilaian ternyata memang benar hasil belajar siswa masih di bawah standar KKM.Kata Kunci— powerpoint, realistic mathematics education, Pemahaman Siswa